1994
DOI: 10.1128/jvi.68.3.1935-1941.1994
|View full text |Cite
|
Sign up to set email alerts
|

Structure of intracellular mature vaccinia virus observed by cryoelectron microscopy

Abstract: Intracellular mature vaccinia virus, also called intracellular naked virus, and its core envelope have been observed in their native, unfixed, unstained, hydrated states by cryoelectron microscopy of vitrified samples. The virion appears as a smooth rounded rectangle of ca. 350 by 270 nm. The core seems homogeneous and is surrounded by a 30-nm-thick surface domain delimited by membranes. We show that surface tubules and most likely also the characteristic dumbbell-shaped core with the lateral bodies which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 19 publications
7
43
0
Order By: Relevance
“…Emerging evidence suggests that membrane-proximal protein lattices may be characteristic of enveloped non-icosahedral viruses and may represent an alternative to icosahedral and helical symmetry in virion architecture. For example, cryo-EM and cryoelectron tomography have demonstrated that glycoprotein spikes in the poxvirus core envelope (13,22) and the envelope of hepatitis B virus (20) are hexagonally packed. Retroviral Env may be organized similarly: hexagonal arrays were described for human foamy virus (82), and loose hexagonal packing was noted for human immunodeficiency virus type 1 and simian immunodeficiency virus (89).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that membrane-proximal protein lattices may be characteristic of enveloped non-icosahedral viruses and may represent an alternative to icosahedral and helical symmetry in virion architecture. For example, cryo-EM and cryoelectron tomography have demonstrated that glycoprotein spikes in the poxvirus core envelope (13,22) and the envelope of hepatitis B virus (20) are hexagonally packed. Retroviral Env may be organized similarly: hexagonal arrays were described for human foamy virus (82), and loose hexagonal packing was noted for human immunodeficiency virus type 1 and simian immunodeficiency virus (89).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have noted that surface protein lattices on enveloped virions become disordered with increasing time and temperature. For instance, lattices of Sendai M protein disappeared upon prolonged storage at 37°C (1), while deterioration of vaccinia virus core envelope lattices occurred more slowly during cold storage (22). The kinetics of coronavirus lattice disruption and effects on infectivity are unknown and will require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Not depicted are corroborative DEEM images we have obtained of purified vaccinia virus cores generated by detergent extraction of isolated IMVs, in which case the lateral bodies are retained on the surface of the cores and thus are fully exposed and immediately apparent. They are clearly not an artifact, as one group once claimed (Dubochet et al, 1994).…”
Section: Cross Fractures Of Viral Coresmentioning
confidence: 93%
“…Moreover, we should have expected to see some sort of pattern of intramembrane particles on its fracture faces, if it had existed. This is because several earlier EM studies have shown that the clear zone around the core of IMVs is punctuated by a very distinctive array of "spicules", which has lead to its having been named the palisade layer (Easterbrook, 1966;Muller and Williamson, 1987;Dubochet et al, 1994). Such a palisade would surely be expected to yield some sort of regular pattern of intramembrane particles on the fracture face of the membrane to which it attached (again, if such a membrane existed).…”
Section: Deeper Cross Fractures Into Imvsmentioning
confidence: 99%
“…However, fine, well-preserved details on the surface of viruses were appreciated only in Ta replicas. The reason for this is that although negative staining is a very useful method that provides medium resolution when dealing with non-enveloped viruses and macromolecular complexes, it can be too disrupting for non-fixed membranous structures, such as viral envelopes (Dubochet et al, 1994;Harris and Scheffler, 2002;Kiselev et al, 1990).…”
Section: Resultsmentioning
confidence: 99%